Active Control of the Space-borne Antenna Reflector Considering Thermal Load. Issue 1 (April 2021) - Huang, Rui; Sun, Beibei
Abstract: In order to improve the shape accuracy of the space-borne antenna reflector under the interference of uncertain load, the active control method of the reflector shape was studied. First, a finite element model of the thermal and mechanical coupling of the space-borne antenna reflector was established. Taking the uncertain load into account, the radial basis function (RBF) neural network was used to estimate the error, and the adaptive controller was designed according to the estimation error. Based on the Lyapunov stability theory, the stability of the controller was analyzed. Finally, the adaptive control of the space-borne antenna reflector was simulated numerically. The simulation results show that the method of RBF neural network adaptive control is effective by reducing the shape error of the reflector in a short time when considering the uncertain load.